Prevention of labor complication via the improvement of vaginal microbiocenosis - L.Yu. Karakhalis; N.S. Ivantsiv (LCC «Medicine-Inform», 2021)
L.Yu. Karakhalis, N.S. Ivantsiv Kuban State Medical University, Krasnodar, Russian Federation Aim: to assess the effect of Lactobacilli on vaginal microbiocenosis in pregnant women with its pre-existing disturbances manifested as an increase in vaginal pH levels (>4.5) and pathological vaginal discharge in the 1st trimester of pregnancy. Patients and Methods: a prospective study involved 261 pregnant women who registered their pregnancy before 14 weeks. Group 1 included 147 women with vaginal pH>4.5 and gray white smelling discharge, but no cornified squamous epithelial cells and negative whiff test. Group 2 included 114 pregnant women with vaginal pH 3.8-4.5 and no vaginal discharge. At 11-14 weeks, 18-21 weeks, 30-34 weeks, and before delivery (36-41 weeks), vaginal pH, the composition of opportunistic flora, and Lactobacilli count were evaluated. In group 1, intravaginal lyophilized culture of L. casei rhamnosus (LCR) Doderleini was prescribed after each screening and before the delivery (in total, 4 courses). Results: the use of LCR preparation throughout the gestation reduced vaginal pH from 4.9 (11-14 weeks) to 4.5 (36-41 weeks) (p=0.001). In group 2, vaginal pH increased from 4.35 to 4.7 (p=0.000). In group 1 (probiotic containing LCR Lactobacilli was prescribed), the percentage of women with isolated L. jensenii strain increased by 1.6 times (from 9.52% to 14.96%). Meanwhile, in group 2 (no probiotic was prescribed), the percentage of women with isolated L. jensenii strain reduced by 4.2 times (from 14.91% to 3,51%; p=0.000). In group 1, abnormal birth activity and premature rupture of membranes were reported significantly less common (р=0.0001 and р=0.0001, respectively). Conclusions: probiotic containing LCR is favorable in terms of reducing the rate of pregnancy and birth complications. This fact is of particular importance for women who are at risk of bacterial vaginosis. Keywords: pregnancy, Lactobacilli, vaginal microbiocenosis, pH measurement, probiotics. For citation: Karakhalis L.Yu., Ivantsiv N.S. Prevention of labor complication via the improvement of vaginal microbiocenosis. Russian Journal of Woman and Child Health. 2021;4(1):31-35. DOI: 10.32364/2618-8430-2021-4-1-31-35.